SKRINING POTENSI ANTIJAMUR DARI JAMUR SIMBION SPONS TERHADAP JAMUR Trichophyton Sp. - Popi Ida Laila Ayer; Korinus Rejauw; Ervina Indrayani (Cenderawasih University, 2021)
Sponges are marine organisms that are filter feeders so that they become a habitat for microorganisms. Microorganisms symbiont and sponge produce secondary metabolites as self-protection mechanisms which are then used to find active compounds that are useful for medicine (pharmacology). The aim of this study was to isolate the active fraction of the fungal symbiont sponge and Characterization mikroskopiks of fungal symbionts sponge which has bioactivity as antifungals against Trichophyton sp. Sponge was taken from Opiaref Sea, Biak Numfor, Papua. Fungal symbiont of sponges was isolated by direct plate method. Purification of fungal symbiont was conducted by streak-plate method. Bioactivity assay of fungal symbiont sponges against Trichophyton sp. was conducted by agar diffusion method. Purification of bioactive compound was conducted by separatory funnel, TLC and OCC. Characterization of fungal symbionts sponge by mikroskopiks. Fungal symbiont from sponge C1K1 has best bioactivity as antifungal against Trichophyton sp. are fungi with the isolates MT.C12 and MT.C14. Isolation of bioactive compound obtained 2 fractions that best in inhabiting fungi Trichophyton sp. Diameter of inhibition zone of MT.C12-1-6 (13,44 mm) and MT.C14-1-4 (7,43 mm). TLC visualization with vanilin sulfuric acid indicated that MT.C12-1-6 and MT.C14-1-4 fraction form pink spots. Based on the color formed on both fractions containing alkaloids. Alkaloids are compounds that have biological activity of and provide certain physiological effects on organism.